IMPLEMENTASI PEMBELAJARAN KETERAMPILAN MENARI SISWA SMP DALAM PANDANGAN PRAGMATISME DAN BEHAVIORISME ( STUDI KASUS DI SMP NEGERI 21 KOTA SURAKARTA) - Wegang Sri Sulanjari; Lukit Adi Syam Ari; M. Yusup Supriyadi; Eni Nur Khikmah; Endang Fauziati (Jurnal Kependidikan, 2025)
This research is an attempt to improve the dancing skill of the students, which is based on pragmatic approaches and theories of behaviorism. Pragmatic approaches are taken in order to convince the students of the effect of practice, while theories of behaviorism are consulted to understand the reactions of the students to the a number of technique. This article describes the process of the research, involving observations, interviews, and documentations with the teachers and the students of the class VIII of SMP Negeri 21 in Surakarta, and then presents the results of the analysis. It has turned out that drills and modelling if practiced regularly and continuously, improve the dancing skill of the students, not only with regard to physical movements (wiraga), but also expressions (wirasa) and the understanding of the accompaniment (wirama). Those results show that the drill and modelling technique with pragmatic approaches and theories of behaviorism is effective to improve the dancing skill of the students of SMP Negeri 21 in Surakarta.